The Limits of Resilience and the Need for Resistance: Articulating the Role of Music Therapy With Young People Within a Shifting Trauma Paradigm - Scrine, Elly (Frontiers in Psychology, 2021)
A broad sociocultural perspective defines trauma as the result of an event, series of events, or set of circumstances that is experienced as physically or emotionally harmful or life threatening, with lasting impacts on an individual’s physical, social, emotional, or spiritual wellbeing. This perspective informs trauma-informed practice which strives to attend to the complex impacts of trauma, integrating knowledge into policies and practices, and providing a sanctuary from harm. However, there is a body of critical and decolonial scholarship that challenges the ways in which trauma-informed practice prioritizes individualized interventions, conceptualizes safety in a way that reinscribes colonial power relations, and obscures the role of systemic injustices. Within music therapy trauma scholarship, research has thus far pointed to the affordances of music in ameliorating symptoms of trauma, bypassing unavailable cognitive processes, and working from a strengths-based orientation. In critiquing the tendency of the dominant trauma paradigm to assign vulnerability and reinforce the individual’s responsibility to develop resilience through adversity, this conceptual analysis outlines potential alternatives within music therapy. Drawing on a case example from a research project with young people in school, I elucidate the ways in which music therapy can respond to power relations as they occur within and beyond ‘trauma-informed’ spaces. I highlight two overarching possibilities for music therapy within a shifting trauma paradigm: 1) as a site in which to reframe perceived risk by fostering young people’s resistance and building political agency, and 2) in challenging the assumption of ‘safe spaces’ and instead moving towards practices of ‘structuring safety’.